Brown Dog Tick Rhipicephalus sanguineus Latreille (Arachnida: Acari: Ixodidae) - Yuexun Tian; Cynthia Lord; Phillip E. Kaufman (EDIS)
The brown dog tick is unusual among ticks in that it can complete its entire life cycle indoors as well as outdoors. Brown dog tick infestations can develop in dog kennels and residences, where populations can reach dramatic levels and cause dog diseases. This 6-page fact sheet written by and published by the UF/IFAS provides the distribution, description and identification, life cycle, and management of the brown dog tick as well as its hosts and the medical and veterinary significance of this troublesome pest. https://edis.ifas.ufl.edu/in378